2005
DOI: 10.1007/s11664-005-0095-4
|View full text |Cite
|
Sign up to set email alerts
|

Ion bombardment-induced high orientation of Al/Ti films for surface acoustic wave device applications

Abstract: Al/Ti films were deposited on 128°Y-X LiNbO 3 substrates by electron-beam (e-beam) deposition. Low-energy Ar ion beam bombardment was employed during the Ti underlayer deposition. Influence of low-energy beam bombardment on the texture of Al/Ti films was investigated by x-ray diffraction (XRD) analysis. It was found that Al films deposited on Ar-ion bombarded Ti underlayers possessed excellent (111) texture. With the textured Al/Ti films, a 2.3-GHz range image-impedance connection surface acoustic wave (SAW) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…We obtained highly textured Al (111) films on a Ti underlayer using the IBAD technique. 8 In the present case, the Al (111) orientation of the Al-Zr alloys on the Ti underlayer was improved using the sputtering technique by controlling the sputtering pressure. Figure 6 shows the effect of the orientation of the Al-0.2%(wt.%)Zr/Ti electrode film on lifetime.…”
Section: Effect Of Microstructure On Lifetime Of Al-zr/ti Electrode Fmentioning
confidence: 93%
See 1 more Smart Citation
“…We obtained highly textured Al (111) films on a Ti underlayer using the IBAD technique. 8 In the present case, the Al (111) orientation of the Al-Zr alloys on the Ti underlayer was improved using the sputtering technique by controlling the sputtering pressure. Figure 6 shows the effect of the orientation of the Al-0.2%(wt.%)Zr/Ti electrode film on lifetime.…”
Section: Effect Of Microstructure On Lifetime Of Al-zr/ti Electrode Fmentioning
confidence: 93%
“…6,7 The ion-beam-assisted deposition (IBAD) technique was employed to improve the crystallinity of Al and the mechanical properties of Al/Ti bilayered films. 8,9 In this paper, both Zr-doped Al and a Ti underlayer were deposited by radiofrequency (RF) sputtering on ferroelectric 128°Y-X LiNbO 3 substrates, which were expected to increase the power durability of Al electrode films and obtain fine-dimensional control. The effect of microstructure and Zr addition on the failure time, residual stress, and electrical resistivity of the Al-Zr/Ti bilayered films was investigated to improve durability.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors are known to influence thin-film texture evolution through nucleation, growth, substrate material, lattice matching between film and substrate, growth condition, deposition technique, surface morphology of substrate, etc. Low-energy ion bombardment can effectively improve the texture of the films deposited on Ti underlayer [11][12]. In addition, it is reported that Al films deposited on the amorphous layer, which has high surface free energy, show strong (111) texture [13].…”
Section: Microstructurementioning
confidence: 99%
“…Comparatively, as seen in Table 1, Mo and Ti as additive elements are more compatible with dry etching using chlorinated gases because of the low boiling temperature of MoCl 5 and TiCl 4 . On the other hand, it is reported that a layer such as a combination of Al and a refractory metal might provide high reliability and adhesion to the substrates [11]. Therefore, a new 4-layered Ti/Al-Mo/Ti/Al-Mo electrode was developed in this paper.…”
Section: Introductionmentioning
confidence: 99%